THE MECHANISMS OF STATE YOUTH POLICY MODEL JUSTIFY IN THE CONTEXT OF A LARGER CROSS-BORDER COOPERATION OF UKRAINE - Kozhushko N.I. (Pressing Problems of Public Administration, 2015)
The content of the national youth models due to the possibility of adapting to the challengesof the integration process state to the international community, particularly in terms of expansionof cross-border cooperation.